HISTO- AND CYTOARCHITECTONICS OF SPLEEN DURING THE ADMINISTRATION OF ANTIHISTAMINE DRUGS - Дудок, О.В.; Луцик, О.Д. (World of Medicine and Biology, 2015)
Introduction. Currently a variety of xenobiotics, including different type drugs, to which population is exposed, increase rapidly. Additionally to therapeutic effect, drugs oftenly cause deteriorating effect on individual organs. Therefore the investigation of adverse influence of drugs, especially those that are readily available and are used without a prescription, is actual. Objective. The aim of present investigation was to study the micromorphology of spleen during the administration of therapeutic doses of antihistamine drug Loratadine. Materials and methods. Experiments were performed on 16 Wistar rats in two groups. The first group - 8 animals - intact rats. The animals of the second group once a day during 30 days were administered intragastrically Loratadine at a dose of 0.15 mg/kg body weight. On days 10th and 30th halph of experiment animals were killed by cervical dislocation under general ether anesthesia, and spleen samples were collected for morphological studies. The histological material was fixed in 4% neutral formalin and embedded in paraffin. Sections 5-7 mkm thick were stained with hematoxylin and eosin. Microscopy was performed using a Leica DM2500 microscope supplemented with Leica DFC450C camera. Results and discussion. Microscopical investigation of intact rats spleen revealed typical structure for this animal species, namely, well-developed elements of the white pulp and structured red pulp. Spleen of rats after 10 days of Loratadine treatment expressed no significant structural changes, except of some expansion of venous sinuses, red pulp hyperemia and accumulation of erythrocytes in within cords of Billroth. No evidence of antigenic stimulation of the white pulp has been detected. On the day 30th of experiment these changes progressed. Increased amount of cellular elements of the white pulp was accompanied by the increased number of lymphoid follicles with well-defined germinal centers. Also it was detected hypertrophy of Billroth cords. However, the reported changes do not indicate a deep destruction of splenic tissue and are likely to be transient. Conclusions. Our results demonstrate that oral administration of Loratadine during 30 days in rats did not cause significant pathological changes in the structural organization of the spleen. However, taking into consideration cumulative properties of Loratadine, further examination of spleen after more prolonged administration of this drug will be of interest.